Innovative AETCOM session on health care as a right: Experience at the medical college in Puducherry - Chandar Sahanaa; Rajasekar Niranjan; Kumar Pradeep; Samundeswari Gopinath; Elanchezhian Dhanasekar; Sengadhir Vendhan; Vasanthakogilam Maniradjou; Rajesh Kumar Konduru; Manjiri Phalsalkar (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Attitude, Ethics, and Communication (AETCOM) module 2.3 is effective in improving the communication skills of medical students, which in turn will prevent malpractices and litigations against doctors. Module 2.3, 'Health Care as a Right,' was aimed at introducing healthcare systems, access, equity in access, the impact of socio-economic situation in determining healthcare access, the role of doctors as key players, and the missing links in the health care systems to students. MATERIALS AND METHODS: A teaching and learning activity was developed for MBBS professional year 2 on AETCOM 2.3. The activities planned were an introduction to the topic, a short documentary film using AV aids, role play by the team, group discussion followed by role play by the students, reflective writing, and finally summarizing the session with a take-home message. RESULTS: The number of responses received in reflective writing was 114. The thematic analysis of qualitative responses was grouped into categories The facilitating factors were the availability of trained doctors and round-the-clock services, and the hindering factors were disrespect to patients, professional misconduct, long waiting time, etc. The suggestions to improve communication between the doctor and the patient were to listen politely and develop good rapport. The qualities of a good doctor were good communication skills, empathy, professional conduct, etc. CONCLUSION: This AETCOM session helped the students understand the healthcare delivery system in the country. It changed their attitude toward patients and improved their communication skills as they were soon-to-become doctors.